2007
DOI: 10.1002/rra.978
|View full text |Cite
|
Sign up to set email alerts
|

Instream flows and the decline of riparian cottonwoods along the Yakima River, Washington, USA

Abstract: Under pre-settlement conditions the Yakima River in Washington state, USA was characterized by multiple channels, complex aquifers and extensive riparian cottonwood forests. Subsequent implementation of headwater dams to supply irrigation water has altered river and floodplain processes critical to the cottonwoods and associated riparian vegetation. In this study, we analysed hydrology and floodplain forests and especially the dominant black cottonwoods (Populus trichocarpa) along sequential reaches of the Yak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 35 publications
3
80
1
Order By: Relevance
“…In the Ume River system, in contrast, stress from water tables that remain constantly high during the growing season may be causing long-term reduction in the resilience of S. myrsinifolia鈭抪hylicifolia individuals though not, it would seem, through mechanisms that have, so far, caused a shift in sex ratios. This is in contrast to the findings of Braatne et al (2007) along the Yakima River in Washington (US) who correlated male dominated sex ratios in young P. trichocarpa Torr. and A.…”
Section: Sex Ratioscontrasting
confidence: 99%
“…In the Ume River system, in contrast, stress from water tables that remain constantly high during the growing season may be causing long-term reduction in the resilience of S. myrsinifolia鈭抪hylicifolia individuals though not, it would seem, through mechanisms that have, so far, caused a shift in sex ratios. This is in contrast to the findings of Braatne et al (2007) along the Yakima River in Washington (US) who correlated male dominated sex ratios in young P. trichocarpa Torr. and A.…”
Section: Sex Ratioscontrasting
confidence: 99%
“…As with A. negundo, skewed sex ratios have been observed in many populations of Populus (Grant and Mitton 1979;Comtois et al 1986;Braatne et al 1996;Gom and Rood 1999;Braatne et al 2007), but not all (Kaul and Kaul 1984;Stanton and Villar 1996;Rowland and Jackson 2001). In cases where sex ratios occur, males are relegated to more extreme environments (Braatne et al 1996;Rowland and Jackson 2001).…”
Section: The Spatial Segregation Of the Sexesmentioning
confidence: 93%
“…For example, in the Wapato Reach of the Yakima River, the data indicated that the preflow regulation bankfull discharge was sufficiently large to maintain a braided state for the given gradient (Leopold and Wolman 1957), but the current flow regime was more likely to be associated with a meandering or transitional planform (Ferguson 1984;van den Berg 1995). However, flow regulation may be promoting a braided state because of the associated impacts of reduced flow on growth and persistence of floodplain vegetation (Braatne et al 2007) that otherwise provides bank stability (Millar 2000). This outcome suggested that actions leading to development of more stable islands and bars through structures that enhance floodplain deposition and protect revegetation areas could eventually lead to a single dominant, narrower, deeper channel under the present regulated flow regime.…”
Section: Segment Downstream Boundary (Rkm)mentioning
confidence: 96%